Tl(I) adsorption behavior on K-illite and on humic acids. (March 2022) - Ruiz-García, Mismel; Villalobos, Mario; Antelo, Juan; Martínez-Villegas, Nadia
Abstract: Cation sorption on clays and on humic acids (HA) has been extensively documented in scientific literature. Both are important components of natural environments, especially in soils, and therefore, innate competitors in the retention of metallic cations. The aim of this work was to investigate the sorption behavior of thallium (I) on a 2:1 type clay (IMt-2 illite, from silver Hill, Montana), and to compare it with its sorption behavior on HA. For this, a total of nine sorption isotherms of thallium on illite and/or HA were conducted at different pH values (3, 7 and 9). The sorption mechanism on illite was investigated by designing a novel cation exchange sorption model that incorporates an additional surface complexation mechanism (2pKa/3CE), where selectivity coefficients for 3 different types of exchange sites and a surface complexation constant for a pH-dependent site (≡SOH) at illite particle edges were obtained. In the case of Tl complexation by HA, investigation of the mechanism involved was done using the NICA-Donnan model. Sorption to illite showed increasing Tl + uptake upon increasing pH from 3 to 9 by approximately one order of magnitude. Tl + sorption on HA was also highly pH dependent, but slightly lower than on illite, although at low pH Tl + complexation on HA was negligible. Geochemical sorption modeling on illite suggests that at very low Tl + concentrations cation exchange Frayed Edge Sites were dominant at all pH values, after which at pH 3 and 7 the other interlayer cation exchange sites became the major contributors to sorption; while at pH 9 surface complexation of Tl(I) on the edge sites predominated, confirming the important variable-charge nature of illite and the strong competition that protons exert for binding of Tl(I) on these sites. In the case of modeling the Tl(I) binding to HA, complexation with the phenolic groups or high affinity sites present at the HA surfaces was predicted to be dominant, although at pH 7, the electrostatic component was dominant at the higher Tl + concentration interval. The findings in this work contribute to further the understanding of two crucial geochemical mechanisms of Tl(I) retention in contaminated soils. Highlights: Tl  +  sorption on both illite and HA showed a strong dependence with pH. A higher binding affinity occurred on illite than on HA. Interlayer sites of illite dominated sorption at pH 3 and 7. Variable charge sites on illite edges dominated sorption at pH 9. Sorption on HA was dominated by phenolic sites, and the electrostatic component at pH 7.